Anti-aging wear-resistant PE plate and production process thereof
Through the synergistic effect of modified antioxidants and zinc white powder, the oxidation chain reaction and mechanical wear are inhibited, and the aging and wear problems of PE plates in outdoor or under high load environments are solved, and the anti-aging, wear resistance and mechanical properties are improved.
Patent Information
- Application Number
- CN202510390230.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-31
AI Technical Summary
Existing PE plates are susceptible to ultraviolet rays, thermal oxygen aging and mechanical wear in outdoor or high load environments, resulting in degradation of mechanical properties, surface powdering cracks and wear resistance.
Modified antioxidants interact with zinc white powder, and the zinc ions on the surface of the thioester group are chelated with zinc ions on the surface of the zinc white powder, inhibit the generation of peroxide at the ultraviolet reflection interface, block the starting point of the oxidation chain reaction, and eliminate the decomposed free radicals by hindered phenol groups to form stable phenol oxygen free radicals, preventing the diffusion of the chain reaction.
The coordinated improvement of anti-aging, wear resistance and mechanical properties is achieved, and the oxidation chain reaction is suppressed for a long time, the migration and segregation of modified antioxidants is reduced, the interface binding capacity of zinc white powder is improved, and the mechanical properties of the composite system are improved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer composite materials, and in particular relates to an anti-aging and wear-resistant PE board and a production process thereof. Background Art
[0002] Polyethylene (PE) sheets are widely used in construction, packaging, automobiles, logistics and other fields due to their advantages such as light weight, chemical corrosion resistance, easy processing and low cost. However, when PE materials are used outdoors or in high-load environments for a long time, they are susceptible to ultraviolet rays, thermal oxidation aging and mechanical wear, resulting in significant decreases in mechanical properties, surface powdering and cracking, and deterioration in wear resistance, which seriously restricts their service life. To this end, the existing technology mainly improves the anti-aging performance of PE sheets by adding antioxidant components, but the traditional technology still has the following defects: Traditional antioxidant systems are mainly based on hindered phenol or thioester organic antioxidants, which inhibit oxidation reactions by capturing free radicals or decomposing peroxides. However, organic antioxidants have a low molecular weight and poor compatibility with the PE matrix. They are easily segregated through migration, seepage, etc. during long-term use, resulting in a sharp decrease in antioxidant efficiency over time. Moreover, taking the traditional hindered phenol and thioester compound system as an example, it can only partially inhibit the different stages of the oxidation chain reaction, but the two lack synergistic effects at the molecular level and it is difficult to block the diffusion of the chain reaction caused by interfacial oxidation.
[0003] In order to make up for the shortcomings of organic antioxidants, the existing technology often introduces inorganic light stabilizers to delay photoaging by reflecting or scattering ultraviolet rays. Although these inorganic particles can reflect most of the ultraviolet rays, their surfaces will still produce multiple reflections and diffuse reflections due to differences in the incident angles of light, especially at the particle-matrix interface to form a local light irradiation enhancement zone. The photothermal oxidation reaction in this area causes the PE molecular chain to break, generating oxidation products such as carbonyl groups, accelerating interface degradation. In addition, the binding ability of these inorganic particles with the PE matrix is not strong, resulting in the inorganic particles falling off during mechanical friction, forming abrasive wear and exacerbating wear. Summary of the invention
[0004] In order to solve the technical problems mentioned in the background technology, the purpose of the present invention is to provide an anti-aging and wear-resistant PE plate and a production process thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions: An anti-aging and wear-resistant PE board comprises: 3.6-4.4wt% zinc white powder, 0.13-0.18wt% modified antioxidant, 1.1-1.4wt% lubricant and 0.7-0.9wt% compatibilizer, and the balance is HDPE resin.
[0006] The modified antioxidant is prepared by the following method: Step A1: premix diethyl thiodiacetate, p-toluenesulfonic acid and anhydrous toluene, add n-alkyl bromide and mix, introduce dry nitrogen protection, heat to 110-120°C, stir and reflux to react for 6-8h, evaporate to remove toluene under reduced pressure after the reaction, cool to room temperature, add saturated sodium bicarbonate solution to wash, remove the aqueous phase and dry in vacuo to obtain an intermediate.
[0007] Further, the feed ratio of diethyl thiodiacetate, n-alkyl bromide, p-toluenesulfonic acid and anhydrous toluene is 10mmol:22-25mmol:0.1-0.13g:60-80mL. Under an acidic catalytic system, n-alkyl bromide and diethyl thiodiacetate undergo an ester exchange reaction to form a thioester containing a brominated alkyl chain. The reaction route is as follows:
[0008] Preferably, the brominated n-alkyl alcohol is one of 8-bromo-1-octanol and 10-bromo-1-decanol.
[0009] Step A2: 3,5-di-tert-butyl-4-hydroxybenzyl alcohol and dimethylformamide are mixed, and then sodium hydride is slowly added and stirred at room temperature for 1-1.5 hours, and then the intermediate is added and the temperature is raised to 80-100°C and stirred for reaction for 3-4.5 hours. After the reaction is completed and cooled, water is added to wash, the water phase is removed and vacuum dried to obtain a modified antioxidant.
[0010] Furthermore, the feed ratio of the intermediate, 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, sodium hydride and dimethylformamide is 10mmol:20mmol:0.15-0.2g:100-150mL. Under the catalysis of sodium hydride, the intermediate and 3,5-di-tert-butyl-4-hydroxybenzyl alcohol are subjected to etherification reaction to introduce terminal hindered phenol structure modification. The reaction route is as follows:
[0011] Preferably, the lubricant is a mixture of calcium stearate and oxidized polyethylene wax, which synergistically lubricates the inside and outside, facilitates the forming of the sheet material, and improves the surface quality of the sheet material.
[0012] Preferably, the compatibilizer is maleic anhydride grafted polyethylene, which improves the dispersibility of each additive and helps to enhance the overall mechanical properties of the board.
[0013] A production process of anti-aging and wear-resistant PE board, including the following steps: Step S1: The raw materials of various components are mixed, and the mixture is plasticized, extruded, drawn into strips, cooled and pelletized to obtain modified PE pellets.
[0014] Step S2: Soften and extrude the modified PE pellets, mold and press them into sheets, and roll them to shape them, so as to obtain anti-aging and wear-resistant PE sheets.
[0015] Furthermore, during the plasticizing extrusion process, the plasticizing temperature is 220±5°C; the softening extrusion temperature is 180±10°C, and the molding pressure is 25MPa.
[0016] Beneficial effects of the present invention: The invention develops a modified antioxidant that interacts with zinc white powder through molecular structure innovation and interface synergistic mechanism, successfully solves the defects of migration loss, interface oxidation and poor dispersibility of traditional antioxidant systems, and realizes the synergistic improvement of anti-aging, wear resistance and mechanical properties. The specific action mechanism is: the thioester group in the modified antioxidant molecule chelates with zinc ions on the surface of zinc white powder, is directly anchored on the surface of zinc white powder, inhibits the generation of peroxides at the ultraviolet reflection interface, blocks the starting point of the oxidation chain reaction, and even if a certain amount of peroxides are generated, the hindered phenol groups at both ends can efficiently remove the decomposed alkoxy free radicals and alkane peroxy free radicals, form stable phenol oxygen free radicals, prevent the chain reaction from spreading, thereby forming a dual synergistic antioxidant mechanism and long-term inhibition of the oxidation chain reaction. At the same time, thanks to the chelating binding effect, the zinc white powder is used as the anchoring matrix, the migration segregation of the modified antioxidant is inhibited, the interface binding ability of the zinc white powder is improved, the interface optimization is formed, the mechanical properties of the composite system are improved, and the shedding and wear of the zinc white powder are inhibited. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Example 1, preparation of anti-aging and wear-resistant PE board, the implementation process is as follows: 1. Synthesis of modified antioxidant Step A1: Take diethyl thiodiacetate, p-toluenesulfonic acid and anhydrous toluene and stir to premix, then add 8-bromo-1-octanol and mix, introduce dry nitrogen protection, heat to 110°C, set the stirring rate to 60r / min, reflux reaction for 8h, during the reaction, control the feed ratio of diethyl thiodiacetate, 8-bromo-1-octanol, p-toluenesulfonic acid and anhydrous toluene to be 10mmol:22mmol:0.1g:60mL, after the reaction is completed, evaporate to remove toluene under reduced pressure, cool to room temperature, add saturated sodium bicarbonate solution to wash, remove the aqueous phase and vacuum dry to obtain an intermediate.
[0019] Step A2: Take 3,5-di-tert-butyl-4-hydroxybenzyl alcohol and dimethylformamide, stir and dissolve them, apply rapid stirring at 120 r / min, slowly add sodium hydride and stir at room temperature for 1.5 hours, then add the intermediate and heat to 80°C, stir and react at 60 r / min for 4.5 hours. During the reaction, the feed ratio of the intermediate, 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, sodium hydride and dimethylformamide is controlled to be 10mmol:20mmol:0.15g:100mL. After the reaction is completed and cooled, water is added for mixing, the aqueous phase is removed and vacuum dried to obtain a modified antioxidant.
[0020] 2. Preparation of PE board Prepare the materials according to the components: 3.6wt% zinc white powder, commercially available 800 mesh coating powder; 0.13wt% modified antioxidant, homemade in this embodiment; 1.2wt% lubricant, mixed with industrial grade calcium stearate and OP-25 type oxidized polyethylene wax in a mass ratio of 2:1; 0.7wt% compatibilizer, 900E type maleic anhydride grafted polyethylene, and the remainder 5000S type HDPE resin.
[0021] Step S1: Add the raw materials of each component into a high-speed mixer and mix them at a high speed of 600r / min for 15min. The mixed material is sent to an extruder, plasticized and extruded at 220±5℃, and then stretched into strips, cooled and pelletized to obtain modified PE pellets.
[0022] Step S2: Soften and extrude the modified PE pellets at 180±10°C, feed the softened material into a flat die, control the pressure to 25MPa to form a molded plate, and then roll-press to shape, thereby obtaining an anti-aging and wear-resistant PE plate.
[0023] Example 2, preparation of anti-aging and wear-resistant PE board, the implementation process is as follows: 1. Synthesis of modified antioxidant Step A1: Take diethyl thiodiacetate, p-toluenesulfonic acid and anhydrous toluene and stir to premix, then add 10-bromo-1-decanol and mix, introduce dry nitrogen protection, heat to 120°C, set the stirring rate to 90r / min, reflux reaction for 6h, during the reaction, control the feed ratio of diethyl thiodiacetate, 10-bromo-1-decanol, p-toluenesulfonic acid and anhydrous toluene to be 10mmol:25mmol:0.13g:80mL, after the reaction is completed, evaporate to remove toluene under reduced pressure, cool to room temperature, add saturated sodium bicarbonate solution to wash, remove the aqueous phase and vacuum dry to obtain an intermediate.
[0024] Step A2: Take 3,5-di-tert-butyl-4-hydroxybenzyl alcohol and dimethylformamide, stir and dissolve them, apply rapid stirring at 150 r / min, slowly add sodium hydride and stir at room temperature for 1 hour, then add the intermediate and heat to 100°C, stir and react at 60 r / min for 3 hours. During the reaction, the feed ratio of the intermediate, 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, sodium hydride and dimethylformamide is controlled to be 10mmol:20mmol:0.2g:150mL. After the reaction is completed and cooled, water is added for mixing, the aqueous phase is removed and vacuum dried to obtain a modified antioxidant.
[0025] 2. Preparation of PE board Prepare the materials according to the components: 4.4wt% zinc white powder, commercially available 800 mesh coating powder; 0.18wt% modified antioxidant, homemade in this embodiment; 1.4wt% lubricant, mixed with industrial grade calcium stearate and OP-25 type oxidized polyethylene wax in a mass ratio of 2:1; 0.9wt% compatibilizer, 900E type maleic anhydride grafted polyethylene, and the remainder 5000S type HDPE resin.
[0026] Step S1: Add the raw materials of each component into a high-speed mixer and mix them at a high speed of 600r / min for 15min. The mixed material is sent to an extruder, plasticized and extruded at 220±5℃, and then stretched into strips, cooled and pelletized to obtain modified PE pellets.
[0027] Step S2: Soften and extrude the modified PE pellets at 180±10°C, feed the softened material into a flat die, control the pressure to 25MPa to form a molded plate, and then roll-press to shape, thereby obtaining an anti-aging and wear-resistant PE plate.
[0028] Example 3, preparation of anti-aging and wear-resistant PE board, the implementation process is as follows: 1. Synthesis of modified antioxidant Step A1: Take diethyl thiodiacetate, p-toluenesulfonic acid and anhydrous toluene, stir and premix, then add 8-bromo-1-octanol and mix, introduce dry nitrogen protection, heat to 110°C, set the stirring rate to 60r / min, reflux reaction for 7.5h, during the reaction, control the feed ratio of diethyl thiodiacetate, 8-bromo-1-octanol, p-toluenesulfonic acid and anhydrous toluene to be 10mmol:23mmol:0.11g:65mL, after the reaction is completed, evaporate to remove toluene under reduced pressure, cool to room temperature, add saturated sodium bicarbonate solution to wash, remove the aqueous phase and vacuum dry to obtain an intermediate.
[0029] Step A2: Take 3,5-di-tert-butyl-4-hydroxybenzyl alcohol and dimethylformamide, stir and dissolve them, apply rapid stirring at 120 r / min, slowly add sodium hydride and stir at room temperature for 1.3 hours, then add the intermediate and heat to 90°C, stir and react at 60 r / min for 4 hours. During the reaction, the feed ratio of the intermediate, 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, sodium hydride and dimethylformamide is controlled to be 10mmol:20mmol:0.17g:120mL. After the reaction is completed and cooled, water is added for mixing, the aqueous phase is removed and vacuum dried to obtain a modified antioxidant.
[0030] 2. Preparation of PE board Prepare the materials according to the components: 3.9wt% zinc white powder, commercially available 800 mesh coating powder; 0.15wt% modified antioxidant, homemade in this embodiment; 1.1wt% lubricant, mixed with industrial grade calcium stearate and OP-25 type oxidized polyethylene wax in a mass ratio of 2:1; 0.8wt% compatibilizer, 900E type maleic anhydride grafted polyethylene, and the remainder is 5000S type HDPE resin.
[0031] Step S1: Add the raw materials of each component into a high-speed mixer and mix them at a high speed of 600r / min for 15min. The mixed material is sent to an extruder, plasticized and extruded at 220±5℃, and then stretched into strips, cooled and pelletized to obtain modified PE pellets.
[0032] Step S2: Soften and extrude the modified PE pellets at 180±10°C, feed the softened material into a flat die, control the pressure to 25MPa to form a molded plate, and then roll-press to shape, thereby obtaining an anti-aging and wear-resistant PE plate.
[0033] Example 4, preparation of anti-aging and wear-resistant PE board, the implementation process is as follows: 1. Synthesis of modified antioxidant Step A1: Take diethyl thiodiacetate, p-toluenesulfonic acid and anhydrous toluene and stir to premix, then add 10-bromo-1-decanol and mix, introduce dry nitrogen protection, heat to 120°C, set the stirring rate to 90r / min, reflux reaction for 7h, during the reaction, control the feed ratio of diethyl thiodiacetate, 10-bromo-1-decanol, p-toluenesulfonic acid and anhydrous toluene to be 10mmol:25mmol:0.11g:80mL, after the reaction is completed, evaporate to remove toluene under reduced pressure, cool to room temperature, add saturated sodium bicarbonate solution to wash, remove the aqueous phase and vacuum dry to obtain an intermediate.
[0034] Step A2: Take 3,5-di-tert-butyl-4-hydroxybenzyl alcohol and dimethylformamide, stir and dissolve them, apply rapid stirring at 150 r / min, slowly add sodium hydride and stir at room temperature for 1.2 hours, then add the intermediate and heat to 90°C, stir and react at 60 r / min for 4 hours. During the reaction, the feed ratio of the intermediate, 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, sodium hydride and dimethylformamide is controlled to be 10mmol:20mmol:0.18g:140mL. After the reaction is completed and cooled, water is added for mixing, the aqueous phase is removed and vacuum dried to obtain a modified antioxidant.
[0035] 2. Preparation of PE board Prepare the materials according to the components: 4.1wt% zinc white powder, commercially available 800 mesh coating powder; 0.16wt% modified antioxidant, homemade in this embodiment; 1.2wt% lubricant, mixed with industrial grade calcium stearate and OP-25 type oxidized polyethylene wax in a mass ratio of 2:1; 0.7wt% compatibilizer, 900E type maleic anhydride grafted polyethylene, and the remainder 5000S type HDPE resin.
[0036] Step S1: Add the raw materials of each component into a high-speed mixer and mix them at a high speed of 600r / min for 15min. The mixed material is sent to an extruder, plasticized and extruded at 220±5℃, and then stretched into strips, cooled and pelletized to obtain modified PE pellets.
[0037] Step S2: Soften and extrude the modified PE pellets at 180±10°C, feed the softened material into a flat die, control the pressure to 25MPa to form a molded plate, and then roll-press to shape, thereby obtaining an anti-aging and wear-resistant PE plate.
[0038] As a comparative example, referring to Example 4, the modified antioxidant was replaced with 0.1 wt % of antioxidant 1010 and 0.06 wt % of antioxidant 412S, and the rest of the implementation process was exactly the same.
[0039] Samples were taken from the plate prepared as above, and tensile properties were tested according to ASTM D638-22, and wear resistance was tested according to ASTM D4060-19. The specific test results are shown in Table 1: Table 1 Tensile strength / MPa Elongation at break / % Wear / mg Example 1 23.9 352 18.3 Example 2 25.7 315 11.9 Example 3 24.5 339 15.5 Example 4 25.1 357 13.6 Comparative Example 24.3 342 14.8 It can be seen from the test results in Table 1 that the above samples all maintain good toughness, and compared with pure PE sheets, the abrasion is no more than 20 mg, and has certain wear resistance; it can be seen from the comparative examples of the test data that with the increase of the proportion of zinc white powder components, the tensile strength and wear resistance show an upward trend, and the elongation at break decreases. Combining Example 4 and the comparative example, the PE board prepared by compounding with the existing combined antioxidant has slightly lower toughness and wear resistance.
[0040] Samples were taken from the plate prepared as above, and accelerated aging tests were carried out according to ASTM G155-21 standard. The test cycle was 2000h. Tensile and wear tests were carried out on the aged samples according to the above standard, and the change rates of the corresponding performance indicators were calculated. The specific test results are shown in Table 2: Table 2 Tensile strength change rate / % Change rate of elongation at break / % Wear change rate / % Example 1 -7.14 -9.11 12.93 Example 2 -4.06 -9.32 14.05 Example 3 -4.82 -5.77 12.19 Example 4 -3.55 -6.08 10.62 Comparative Example -10.29 -18.61 31.74 From the test results in Table 2, it can be seen that after accelerated aging, the tensile strength and elongation at break of the comparative plate decreased significantly, and the wear increased significantly. During the test, a large amount of powder chips were seen falling off.
[0041] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0042] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. An anti-aging and wear-resistant PE board, characterized in that: The specific components are: zinc white powder 3.6-4.4wt%, modified antioxidant 0.13-0.18wt%, lubricant 1.1-1.4wt% and compatibilizer 0.7-0.9wt%, and the balance is HDPE resin; The modified antioxidant is prepared by the following method: Step A1: premix diethyl thiodiacetate, p-toluenesulfonic acid and anhydrous toluene, add n-alkyl bromide and mix, introduce dry nitrogen for protection, heat to 110-120° C., stir and reflux for reaction for 6-8 hours to obtain an intermediate; Step A2: 3,5-di-tert-butyl-4-hydroxybenzyl alcohol and dimethylformamide are mixed, and then sodium hydride is slowly added and stirred at room temperature for 1-1.5 hours, and then the intermediate is added and the temperature is raised to 80-100° C. and stirred for reaction for 3-4.5 hours to obtain a modified antioxidant.
2. The anti-aging and wear-resistant PE board according to claim 1, characterized in that: The feed ratio of diethyl thiodiacetate, n-alkyl bromide, p-toluenesulfonic acid and anhydrous toluene is 10 mmol: 22-25 mmol: 0.1-0.13 g: 60-80 mL.
3. The anti-aging and wear-resistant PE board according to claim 2, characterized in that: The brominated n-alkyl alcohol is one of 8-bromo-1-octanol and 10-bromo-1-decanol.
4. The anti-aging and wear-resistant PE board according to claim 2, characterized in that: The feed ratio of the intermediate, 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, sodium hydride and dimethylformamide is 10 mmol: 20 mmol: 0.15-0.2 g: 100-150 mL.
5. The anti-aging and wear-resistant PE board according to claim 1, characterized in that: The lubricant is a mixture of calcium stearate and oxidized polyethylene wax.
6. The anti-aging and wear-resistant PE board according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polyethylene.
7. A production process for the anti-aging and wear-resistant PE board according to any one of claims 1 to 6, characterized in that: Including the following processes: Step S1: mixing the raw materials of various components, plasticizing and extruding the mixture, stretching and forming strips, cooling and pelletizing to obtain modified PE pellets; Step S2: Soften and extrude the modified PE pellets, mold and press them into sheets, and roll them to shape them, so as to obtain anti-aging and wear-resistant PE sheets.
8. The production process of an anti-aging and wear-resistant PE board according to claim 7, characterized in that: During the plasticizing extrusion process, the plasticizing temperature is 220±5°C; the softening extrusion temperature is 180±10°C, and the molding pressure is 25MPa.
Citation Information
Patent Citations
Anti-aging PE water supply pipe material and preparation method thereof
CN111533984A
UHMWPE modified PE pipe special material
CN116874906A
Polyethylene composite material for plastic bucket and preparation method of polyethylene composite material
CN118165397A
Antioxidant premix for polyethylene and preparation method thereof
CN118620317A
Modified recycled polyethylene plastic for plastic pipeline and preparation method therefor
WO2022088230A1